Preoperative risk factors related to bladder cancer rehabilitation: a registry study - Jensen, B T; Laustsen, S; Petersen, A K; Borre, M; Soendergaard, I; Ernst-Jensen, K M; Lash, T L; Borre, M (European journal of clinical nutrition, 2013)
Introduction: Patients diagnosed with (muscle-) invasive bladder cancer (IBC) are more likely to harbour comorbidities due to their advanced age at diagnosis. Under-nutrition is a predictor for postoperative morbidity and mortality in cancer patients, but under-reported in urology. Understanding the IBC patient profile before major surgery could facilitate and optimise outcome of the surgical patient. Background/objectives: To identify preoperative risk factors for early rehabilitation before radical cystectomy (RC). Subjects/methods: A historical registry-based study of 76 patients referred for RC at Aarhus University Hospital, Denmark (DK) in 2009. Early rehabilitation was defined by length of stay (LOS) postoperatively with a cutoff ⩽11 days. High comorbidity was expressed by the charlson comorbidity index score (CCI) ⩾3. LOS was calculated by linking the unique Civil Registration Number with the National Patient Registry. Preoperative nutritional risk was identified using the screening tool, nutritional risk score 2002 (NRS) of the European Society of Clinical Nutrition and Metabolism. Multivariate analysis was used to identify risk factors for early rehabilitation. Results: The proportion of patients at preoperative nutritional risk was 26% (95% confidence interval (CI): (95% CI: 17; 37) and 43% of patients held a high CCI (95% CI: 33; 55). Prolonged LOS was independently associated with female gender ( P =0.02) and age ⩾70 years ( P =0.04). NRS and CCI were not associated with LOS. Conclusions: Attention should be focused on women and elderly patients undergoing RC to optimise early rehabilitation and reduce LOS. It is still unknown whether preoperative nutritional risk and comorbidity are obstacles in early rehabilitation of RC patients.